Ottoman architecture: |a reappraisal of the European influences - Thys, Lucienne Marie. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 1986., 1986)
The following thesis investigates the dynamics of architectural change that occurred in the Ottoman capital during the nineteenth century. This era of Ottoman history is a highly complex one, characterized by tremendous political, social as well as architectural and urban changes. Traditionally, it has also been an era that has been perceived by most Ottoman historians as one of decline. In recent scholastic works, however, historians are reevaluating the events of the last century of the Empire's existence and allowing for other, more complex, frameworks of historical analyses other than that of a gradual decline. My own interest in the architecture of this period began because I continually found in the architectural history written about the nineteenth century structures of Istanbul that this bias of a historical decline was generally the basic starting point for most scholars of nineteenth century Ottoman architecture. Occasionally, one finds buildings designed by Ottoman architects are cursorily dismissed as "degenerate" or "bombastic" European imitations. l Alternatively those structures built by European architects working in the capital city of the Empire are seen as concrete manifestations of European imperialistic ambitions in the Near East. 2 Too often the architectural works of the last century are allotted a few pages at the back of a book on Ottoman architecture or, worse yet, completely ignored. In order to better understand the architecture built during this era of great change and transition, I suggest that we put aside our traditional historical and political biases and broaden our avenues of inquiry in a number of ways. First, any study of nineteenth century Ottoman architectural history must include an investigation into the corresponding architectural movements of Europe. Several of the Ottoman palace architects, who built during the nineteenth century. if they were not Europeans themselves, were trained in Europe. Additionally, the patrons of many of Istanbul's nineteenth century structures were members of the Empire's European community that was located in the Galata area. In order to fully understand the European influence on Ottoman architecture and the synthesis of the two, a knowledge of architecture in both regions is necessary. Secondly, an obvious point but one that is many times overlooked, is that architecture can be used as an invaluable measure of historical change. It is essential, however, that it be treated differently than documents, treaties, wars and other standard materials historians use to help reconstruct history. Architecture and art have another dimension - that of the aesthetic which requires additional tools of analysis and sometimes a very different framework altogether. It is for this reason that the discipline of art history has emerged in the last century. While peoples and languages may be divided by borders, artistic changes are extremely fluid and generally do not remain constricted by geographical or political boundaries. Thirdly, we must remember that the very essence of architecture lies in its composite nature. All architects draw inspiration and ideas from previously built structures either by adopting, rejecting or somehow modifying earlier architectural concepts. In some eras, such as the nineteenth century, the eclectic nature of artistic creations was greater than in other centuries where individuality and uniqueness in architectural expression was more highly valued. Architects, both European and European-trained Ottomans, designed their buildings according to a set of architectural principals which encouraged the use of a variety of historicizing architectural motifs. This historicizing eclecticism eventually evoked a reaction among twentieth century architects and architectural historians alike. Thus, one must be careful, not to let the biases of the present century minimize the achievements of architects who built a century earlier when a different type of architecture was valued. In the final analysis, the architects working in Istanbul during the nineteenth century were the builders of new types of buildings in the Empire: palaces, military barracks, train stations, apartment buildings, hotels, banks and government buildings. Some of these architects acted as mediators of culture and technological change between Europe and the Ottoman Empire: others were responsible for the foundation of the architectural schools in the Empire that trained and produced the first members of the new Turkish architectural profession. In short, both the Ottoman and European architects of nineteenth century Istanbul "planted the seeds of a new architectural era and thus should rightly be considered the bridges between the old world and the new."
Keywords: Islamic architecture -- Turkey.; Architecture, Ottoman -- Turkey.; Architecture, Turkish.